First record of Cassiopea xamachana ephyrae from the wild in India, with insights into its life history and development - L. Ranjith; Raju Saravanan; K.S. Sobhana; I. Jagadis; S. Ramkumar; C. Kalidas; D. Linga Prabu; M. Kavitha; P. Nevathitha; A. Mathan Babu; D. Sarathapriya; L. Loveson Edward; et al. (Regional Studies in Marine Science, 2026)

Nicotinamide riboside supplementation restores microglial health and improves cognition in aged male mice - Ramkumar Thiyagarajan; Rupadevi Muthaiah; Bhavana Sreevelu; Owen P. Treanor; Yonas Redae; Reem Berman; Anna L. Davis; Nanda Yellapu; Spencer R. Rosario; Lee D. Chaves; Kenneth L. Seldeen; Bruce R. Troen (GeroScience, 2025)
Cognitive impairment affects 1 in 6 individuals over 60, with over 75 million projected by 2030. Age-related changes in microglial function and declining nicotinamide adenine dinucleotide (NAD + ) levels may contribute to cognitive decline. Although nicotinamide riboside (NR) supplementation can restore NAD + levels in aged mice, its effects on microglial phenotype and cognition during normal aging remain unclear. We assessed cognitive function, neuroinflammation, and microglial gene expression in 6-month (Young) and 22-month (Aged) mice, along with aged mice supplemented with NR (Aged + NR; 400 mg/kg body weight) for 8 weeks. Aged mice exhibited impaired cognition and increased gene expression related to neuroinflammation. NR supplementation improved or prevented the decline in nest-building ability, Y-maze spontaneous alternation, and novel object recognition, which are reflective of instrumental activities of daily living, spatial working memory, and recognition memory. NR supplementation diminished microglial (IBA1) and astrocytic (GFAP) activation, resembling the young phenotype. Gene expression profiling revealed reduced microglial activation, inflammatory pathways, and chemokine production in Aged + NR mice, along with upregulation of genes associated with learning, memory, and gliogenesis. NR lowered transcriptional signatures from age-dependent (ADEM) and disease-associated (DAM) microglia and enhanced homeostatic state profiles. Metabolic pathway analysis of microglial transcripts indicated that NR suppressed age-induced increases in fatty acid metabolism. This was supported by immunostaining, which showed reduced lipoprotein lipase (LPL), a DAM marker, in the cortex and hippocampus. Overall, NR appeared to mitigate age-related cognitive decline by shifting microglial gene expression and metabolism toward a younger phenotype, suggesting potential therapeutic relevance for healthy brain aging.

Fetal response to maternal exposures of environmental chemicals: Utility of a four-cell human feto-maternal interface organ-on-chip - Haley L. Moyer; SungJin Kim; Bowie P. Lam; Lauren S. Richardson; Han-Hsuan D. Tsai; Lucie C. Ford; Hsing-Chieh C. Lin; Weihsueh A. Chiu; Ramkumar Menon; Arum Han; Ivan Rusyn (Chemico-Biological Interactions, 2025)

Textural characteristics of channel bed sediments and heavy minerals of the Cauvery River, Southern India: implications on depositional environments, provenance, tectonics and climate - M. Ramkumar; AL Fathima; G. Sugavanam; B. Velliyangiri; M. Selvakumar; S. Anbarasan; M. Sowmiya; S. Kiruthika; K. Balasubramani; V. Thirukumaran; P. D. Roy; R. Nagarajan; et al. (Journal of Sedimentary Environments, 2025)

Symbiosis in Sea Anemones: A Few Case Reports Along the Bay of Bengal Large Marine Ecosystem - L. Ranjith; R. Saravanan; S. Ramkumar; C. Kalidas; R. Vinothkumar; D. Linga Prabu; M. Kavitha; A. Mathan Babu; R. Kalaibharathi; P. S. Asha (Marine Ecology, 2025)
The most well‐known relationship is between sea anemones and decapod crustaceans, of which crabs are classic examples of mutualistic interactions in which both organisms benefit from living with zooxanthellae and hermatypic or reef‐forming corals. A marine ecology study off the southern coast of Tamil Nadu revealed five types of sea anemones that cohabit symbiotically with other marine animals. These species include Stichodactyla haddoni (Saville‐Kent, 1893), Entacmaea quadricolor (Leuckart in Ruppell and Leukart, 1828), Radianthus (= Heteractis ) magnifica (Quoy and Gaimard, 1833), Radianthus (= Heteractis ) crispa (Ehrenberg, 1834), and Calliactis polypus (Forsskal, 1775), are found in symbiotic associations. This observation revealed that the decapod porcelain crab Neopetrolisthes is associated with the sea anemones Radianthus and Entacmaea , whereas this has not been reported in Stichodactyla . The hermit crab anemone, C. polypus , is generally associated with hermit crabs, and we report this association for the first time in live gastropod, Turbinella pyrum (Linnaeus, 1767). A few animals (both the host and symbiont) were brought to the cnidarian laboratory at the ICAR‐Tuticorin Regional Station of the CMFRI, where they were maintained in optimum seawater for further observations. The present study aimed to compare previous reports of symbiosis in decapod crustaceans and gastropods with sea anemones from Indian waters to provide insight into the dynamics of symbiosis in the Bay of Bengal Large Marine Ecosystem.

Forecasting influent wastewater quality by chaos coupled machine learning optimized with Bayesian algorithm - D. Ramkumar; V. Jothiprakash (Journal of Water Process Engineering, 2024)

Multifunctional Nanocarriers for Alzheimer’s Disease: Befriending the Barriers - Mohammad Azam Ansari; Takshashila Tripathi; Baskar Venkidasamy; Alan Monziani; Govindasamy Rajakumar; Mohammad N. Alomary; Sami A. Alyahya; Oriane Onimus; Naomi D’souza; Md. Abul Barkat; Ebtesam A. Al-Suhaimi; Ramkumar Samynathan; et al. (Molecular Neurobiology, 2024)

A chaotic investigation on pollutant parameters of a wastewater treatment facility using false nearest neighbour algorithm - D. Ramkumar; V. Jothiprakash (Stochastic Environmental Research and Risk Assessment, 2024)

Discovery of pyrrolo[2,1-f][1,2,4]triazine-based inhibitors of adaptor protein 2-associated kinase 1 for the treatment of pain - Carolyn D. Dzierba; Bireshwar Dasgupta; George Karageorge; Walter Kostich; Brian Hamman; Jason Allen; Kim M. Esposito; Ramesh Padmanabha; James Grace; Kimberley Lentz; John Morrison; Daniel Morgan; et al. (Medicinal Chemistry Research, 2023)

Integrated system to reduce emissions from natural gas-fired reciprocating engines - Hafiz Ahmad Hassan; Matthew Hartless; Mohammed A.Moinuddin Ansari; Carlos D. Pena; James D. Lynch; Pejman Kazempoor; Ramkumar N. Parthasarathy (Journal of Cleaner Production, 2023)

Genetic diversity analysis of wild and cultivated Rosa species of India using microsatellite markers and their comparison with morphology based diversity - Abhay Kumar Gaurav; Namita; D. V. S. Raju; M. K. Ramkumar; M. K. Singh; Bhupinder Singh; S. Gopala Krishnan; Sapna Panwar; Amitha Mithra Sevanthi (Journal of Plant Biochemistry and Biotechnology, 2022)

Cross-sectional study on rotavirus A (RVA) infection and assessment of risk factors in pre- and post-weaning piglets in India - O. R. VinodhKumar; S. Sircar; B. S. Pruthvishree; K. R. Nirupama; B. R. Singh; D. K. Sinha; Ramkumar Rupner; A. Karthikeyan; R. Karthikeyan; Z. B. Dubal; Y. S. Malik (Tropical Animal Health and Production, 2020)

Assessing differential vulnerability of communities in the agrarian context in two districts of Maharashtra, India - Bhavana Rao Kuchimanchi; Divya Nazareth; Ramkumar Bendapudi; Suchita Awasthi; Marcella D’Souza (Climate and Development, 2019)

Methamphetamine Induces Apoptosis of Microglia via the Intrinsic Mitochondrial-Dependent Pathway - Anna V. Sharikova; Elizabeth Quaye; Jun Yong Park; Maxwell C. Maloney; Habben Desta; Ramkumar Thiyagarajan; Kenneth L. Seldeen; Neil U. Parikh; Parteet Sandhu; Alexander Khmaladze; Bruce R. Troen; Stanley A. Schwartz; et al. (Journal of Neuroimmune Pharmacology, 2018)

Influence of hydrogeochemical processes and assessment of suitability for groundwater uses in Busan City, Korea - S. Y. Chung; S. Venkatramanan; T. H. Kim; D. S. Kim; T. Ramkumar (Environment, Development and Sustainability, 2015)

Genetic structure and diversity of India hybrid tea - S. N. Raina; P. S. Ahuja; R. K. Sharma; S. C. Das; P. Bhardwaj; R. Negi; V. Sharma; S. S. Singh; R. K. Sud; R. K. Kalia; V. Pandey; J. Banik; et al. (Genetic Resources and Crop Evolution, 2012)

The molecular diversity and evolution of Rice tungro bacilliform virus from Indian perspective - Satendra K. Mangrauthia; P. Malathi; Surekha Agarwal; B. Sailaja; Jagrati Singh; G. Ramkumar; D. Krishnaveni; S. M. Balachandran (Virus Genes, 2012)

Genetic variation of coat protein gene among the isolates of Rice tungro spherical virus from tungro-endemic states of the India - Satendra K. Mangrauthia; P. Malathi; Surekha Agarwal; G. Ramkumar; D. Krishnaveni; C. N. Neeraja; M. Sheshu Madhav; D. Ladhalakshmi; S. M. Balachandran; B. C. Viraktamath (Virus Genes, 2012)

Persistence and Dissipation Kinetics of Deltamethrin on Chili in Different Agro-Climatic Zones of India - Suneet Pandher; S. K. Sahoo; R. S. Battu; Balwinder Singh; M. S. Saiyad; A. R. Patel; P. G. Shah; C. Narendra Reddy; D. Jagdishwar Reddy; K. Narasimha Reddy; Ch. Sreenivasa Rao; Tirthankar Banerjee; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Genetic characterization of 2006–2008 isolates of Chikungunya virus from Kerala, South India, by whole genome sequence analysis - E. Sreekumar; Aneesh Issac; Sajith Nair; Ramkumar Hariharan; M. B. Janki; D. S. Arathy; R. Regu; Thomas Mathew; M. Anoop; K. P. Niyas; M. R. Pillai (Virus Genes, 2010)

Barium anomaly preceding K/T boundary: possible causes and implications on end Cretaceous events of K/T sections in Cauvery basin (India), Israel, NE-Mexico and Guatemala - M. Ramkumar; M. Harting; D. Stüben (International Journal of Earth Sciences, 2005)